Immigrants in Auckland : a contribution to human ecology : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Geography at Massey University - Trlin, Andrew D. (Massey University, 1974)
New Zealand's post-war pattern of immigration and immigrant settlement has been characterised by three features. First, although British immigrants still formed the dominant group of new arrivals, the migrant stream has included a broader spectrum of national, cultural, and racial groups. Second, the immigrants have settled mainly in the major urban areas, especially Auckland and Wellington-Hutt. Finally, within the urban areas the various immigrant ethnic and racial groups have become spatially differentiated in terms of their relative residential concentration or dispersal as compared with the host population. Together these features have confronted New Zealanders with a variety of broad social adjustment problems. This study of immigrants in Auckland examines the extent to which intra-urban immigrant residential patterns can be attributed to the operation of four basic factors identified in a review of the seminal literature. The four factors are: (a) the spatial organisation of urban land use; (b) the nature and relative importance of dimensions of (or factors underlying) urban residential differentiation; (c) the the social, cultural and demographic characteristics of the immigrants; and (d) the social and cultural characteristics, attitudes and values, of the host population. It is asserted that these four factors are inter-related and together form a socio-ecological system, wherein there is a close association and interaction between the two dimensions of social distance and physical distance. The operation and interaction of the four factors and the nature of the socio-ecological system as perceived by the writer, are examined via seventeen hypotheses. These hypotheses have been tested largely via (a) case studies of five selected immigrant groups resident within the Auckland Urban Area, and (b) a survey of the attitudes, beliefs and expectations of the host population. The five selected groups - the Dutch, Hungarians, Niueans, Samoans and Yugoslavs - are held to be representative of the broader post-war spectrum of immigrant arrivals. Apart from Chapter 1 which is concerned largely with methodological problems - especially data collection - the findings of this study are reported in six major chapters (Chapters 2 to 7 inclusive). The seventeen hypotheses were either wholly or partially substantiated - only Hypotheses 1, 4, 7 and 15 falling within the 'partially substantiated' category. Thus it is concluded that immigrant intra-urban residential patterns can be attributed to the operation and interaction of the four basic factors listed above. In particular the findings of this study support: (a) the close association of physical and social distance; (b) the role end function of ethnicity as a factor underlying social and physical distances between populations! and (c) the role and function of ethnicity within a cycle of causation that may contribute either positively or negatively to the integrative and/or segregative adjustments of the immigrant and host populations.
Keywords: Immigrants; Immigrants in Auckland; Immigrant adjustment; Immigrant residential patterns